Semi-Empirical (PM3) Study of Conformational Analysis and Electronic Properties of Functionalized Oligohexylthiophenes - Odunola, O.A.; Semire, B. (Asian Journal of Chemistry, 2010)
A semi empirical analysis of a series of 3-hexylthiophenes [3-XHT, where X = Br, NH2, SH, CN, COOH, CONC(CH3)2 and N(CH3)2] having functional group attached to the hexyl substituent up to four monomeric units with head-tail-headtail regioselectivity was carried out. The energy band gap obtained at PM3 level and the results showed that oligomers with 3-(N,N-dimethyl)aminohexylthiophene (3DAHT) present lowest energy band gap although larger that than 3-aminothiophene (3HT). 3DAHT and 3-aminothiophene (3AHT) both with electron donating substituents respond differently when the polymer was torsioned. The electronic donating ability of NH2 through the hexyl carbon-carbon bonds was drastically reduced whereas that of N(CH3)2 was enhanced. The energy band gap changed with the functional group attached to hexyl substituents with some effects on the molecular properties related to electronic conductivity.